High level of growth differentiation factor 15 and lower left ventricular ejection fraction as predictors of left atrial thrombosis in patients with nonvalvular atrial fibrillation. (14th October 2021) - Belokurova, A.V; Gizatulina, T.P; Khorkova, N.Y.U; Martyanova, L.U; Petelina, T.I; Shirokov, N.E
Abstract: Background: The presence of left atrial/left atrial appendage (LA/LAA) thrombus is used as a surrogate marker of potential stroke in patients (pts) with atrial fibrillation (AF). Purpose: To assess the role of growth differentiation factor 15 (GDF-15) level, clinical and echocardiographic (EchoCG) data as predictors of LA/LAA thrombus in pts with nonvalvular AF. Methods: Out of 158 pts with nonvalvular AF admitted to Cardiology Center for radiofrequency ablation or elective cardioversion in 2019–2020 2 groups were formed according to transesophageal EchoCG results: group 1 included pts without LA/LAA thrombus (n=102, mean age 59.5±6.0 years) and group 2 (n=42, mean age 60.9±8.8 years) – pts with LA/LAA thrombus. Arterial hypertension was found in 93 pts of group 1 (91%) and in 40 pts of group 2 (95%, p=0.42), coronary artery disease - in 53 pts (52%) and 29 pts (69%), respectively (p=0.06). Both groups did not differ in frequency and spectrum of oral anticoagulants administration. General clinical assessment, EchoCG, and laboratory tests were performed, including GDF-15 (pg/ml) levels using Human GDF-15/MIC-1 ELISA kit and NT-proBNP (pg/ml) in blood. Results: Pts with LA/LAA thrombus more often had persistent AF, while paroxysmal AF was more common in pts without thrombus. There was a tendency to more significant congestive heart failure in group 2. Mean CHA2DS2-VASc score was higher in pts with LA/LAA thrombus, also there was a tendency to a larger proportion of pts with scores ≥3. According to EchoCG data, sizes and volumes of both atria, right ventricle, end-systolic volume, left ventricular (LV) size, pulmonary artery systolic pressure and LV mass index were higher in group 2; LV ejection fraction (LVEF) was normal in both groups, but it was significantly lower in pts with LA/LAA thrombus: 59.1±5.1 and 64.0±7.3, respectively (p<0.001). GDF-15 and NT-proBNP levels were significantly higher in group 2 compared to group 1: p=0.00025 and p=0.ehab724.048801 respectively. According to ROC analysis cut-off were set at level >935.0 pg/ml for GDF-15 (AUC=0.705, 95% CI 0.609–0.800, p<0.001) and >143 pg/ml for NT-proBNP (AUC=0.759, 95% CI 0.670–0.849, p<0.001). Multivariate logistic regression revealed the following variables as independent predictors of LAAT: GDF-15 >935.0 pg/ml (OR=4.132, 95% CI 1.305–13.084) and LVEF (OR=0.859, 95% CI 0.776–0.951). According to ROC analysis, the model had a good quality: AUC=0.776 (p<0.001), sensitivity was 78.3%., specificity - 78.3%. Conclusion: High level of GDF-15 (>935.0 pg/ml) along with lower LVEF are independent predictors of LA/LAA thrombus in pts with nonvalvular AF. Funding Acknowledgement: Type of funding sources: None.